Treatment tactic of canine cranial cruciate ligament rupture management: A 28-day comparative analysis of ACP and NSAID induced effects on the serum MMP-3 levels and clinical outcomes - K Raulinaite; R Zelvyte; K Skemiene; I Monkeviciene (Veterinární Medicína)
Cranial cruciate ligament rupture (CrCLR) is a common stifle joint pathology among dogs, leading to osteoarthritis and painfulness. Non-surgical treatment options often represent the usage of non-steroidal anti-inflammatory drugs for 14 days (NSAIDs), but autologous conditioned plasma (ACP) shows promising results in managing various orthopaedic conditions, decreasing inflammation, and improving the clinical outcome in dogs. This study aimed to determine the differences in MMP-3 serum levels and the clinical outcomes between differently treated cranial cruciate rupture cases. For this purpose, we used two different treatment methods for managing canine cranial cruciate ligament rupture (minimally invasive ACP injection or oral NSAIDs), and evaluated the clinical outcomes, indicating the quality of life, and the MMP-3 serum levels over a period of 28 days. The findings of this investigation indicate that ACP has better efficacy than two weeks of NSAIDs in inflammation reduction, clinical outcome improvement, and the allowance of a longer duration of activity after 28 days.